Anthocyanins from Agro-waste as Time-Temperature Indicator to Monitor Freshness of Fish Products - Muhammad Oka Ramadhan; Mustika Nuramalia Handayani (ASEAN Journal of Science and Engineering, 2021)
Fish products perish easily due to microbial contamination. Uncontrolled thawing will increase the rate of microbial activity at every 10°C increase in temperature. One of indicator that can detect food quality is the time-temperature indicator (TTI) with changes in pH. However, these indicators are generally made of synthetic chemicals which tend to pollute the environment. This study aimed to summarize various studies on anthocyanins from agro-waste as time-temperature indicator to monitor freshness of fish products. This research used systematic literature review (SLR) from various relevant research and resources. The SLR process includes practical screening, quality appraisal, synthesizing, and reviewing. Anthocyanins derived from agro-waste than can be developed into TTI are purple yam peel, black plums peel, blueberries peel, rambutan peel, sweet potato peel, dragon fruit peel. The TTI from agro-waste anthocyanins can be developed to monitor freshness of fish products.